The Role Of Knowledge Partnerships In Enhancing Organizational Competence - Layth Abdulrazzaq Kamil; Nisreen Abdullah Bdowey; Abdalwahab Abdalfatah Abdalwahab (International Journal of Management Research and Economics, 2024)
This research aims to identify the dimensions of knowledge partnerships and their ability to enhance the organizational competence of the studied organization specifically and organizations in general. Knowledge partnerships contribute to addressing many deficiencies in organizations by strengthening their human, material, and technological resources. The effectiveness of partnerships and the successful achievement of organizational goals largely depend on the ability of managers to select the right partner, who can add value to the organization, engage its members in tasks, and maximize the partner’s capabilities. To address the study's problem, whether knowledge partnerships contribute to enhancing the competence of the organization, the dimensions of trust, knowledge integration, and coordination were identified to measure the impact of knowledge partnerships on organizational competence as the main hypothesis of the study. The descriptive-analytical approach was adopted, utilizing a questionnaire as the primary data collection tool. A total of 49 questionnaires were distributed at the Korek Telecom Company in Nineveh, with its employees serving as the research sample. Several statistical indicators were employed, most notably descriptive and diagnostic methods using mean, standard deviation, and coefficient of variation to achieve precise significance in describing the relationships that could help achieve the study's objectives through the use of the SPSS statistical program. The study raised several questions, the most important being whether the organization can enhance its human, financial, and technological capabilities through partnerships. The study concluded that knowledge partnerships, in all their aspects, significantly affect levels of achievement, thereby enhancing the competitive capabilities of the organization.